Ultrastructural studies on the sensory structures of the larval antennal and maxilla-labial palpi complex of the Oryzaephilus surinamensis (Coleoptera: Silvanidae) - Smita Saha; Prasanta Saha; Subhomoy Roy, et al. (Arthropods)
Oryzaephilus surinamensis L. (Coleoptera: Silvanidae) is an important tropical stored grain pest that inflicts grain damage by acting as an external feeder. .The larva is more voracious feeder than the adults. The sensilla present in the insects antenna and mouth parts can perceive various senses from the environment and host plant. They can act as mechanoreceptors, thermoreceptors hygroreceptors, olfactory receptors and gustatory receptors. Therefore, in the current study, the morphology, structure, and distribution pattern of the sensilla found on the antennae, maxillary and labial palpi of the larvae of O. surinamensis were mainly investigated through scanning electron microscopy Seventeen different types of sensilla, including six types trichoidea, seven types of basiconica, two types of chaetica, one type of styloconica and coeloconica were identified in the antenna of the larvae. Similarly, 23 sub-types of sensilla have been found in the maxillo-labial complex of mouth parts: five types of trichoidea, eight types of basiconica, seven types of styloconica, two types of coeloconica, and one type of digitiformia. In both maxillary and labial palpi sensory complex, a unit of 13 sensilla was identified in which there is always a thick central sensilla encircled by other sensilla. The ultrastructural details of all the sensilla can underlie future electrophysiological and behavioral investigations.